The Effect of Supervisor's Supervision and Assessment of Teacher Performance on School Management Effectiveness (Study at Madrasah Ibtidaiyah Kemiri, Tangerang, Banten, Indonesia) - Anis Fauzi; Nana Suryapermana; Joni Juhaeni (Jurnal Ilmu Manajemen dan Pendidikan, 2022)
This study intends to discuss the effect of supervisor's supervision on the effectiveness of school management, the effect of evaluating teacher performance on the effectiveness of school management, as well as the influence of supervisor's supervision and teacher performance evaluation on the effectiveness of school management. This study was designed using quantitative research methods of multiple linear regression models. The population in this study 102 respondents. The researcher used 20% for research sampling. Additional data was collected through observation and interviews with the principal and the teacher. The results showed that Supervisor's Supervision and Teacher Performance Assessment had a simultaneous effect on Teacher Management, with the results of regression calculations in the form of F-count of 94,703 and F-value of 8,077, and the results of regression coefficient prove that these two independent variables have direct and good conformity and influence of 70.3% on Teacher Administration and 29.7% residuals.